PKM Kelompok Remaja dalam Menerapkan Aplikasi Berbasisis IoT (Internet of Things) untuk Wirausaha Mandiri Berbasis Start-Up - Sapto Haryoko; Hendra Jaya; Mantasia Mantasia; Sutarsi Suhaeb; Badaruddin Badaruddin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Vocational education plays an important role in bridging the gap between educational outcomes and labor market needs, especially in the Industry 4.0 era. With the rapid development of technology, especially artificial intelligence and automation, vocational education must adapt its curriculum to prepare graduates with relevant skills. The Internet of Things (IoT) is one of the key technologies that increases efficiency and opens up new opportunities, especially for the younger generation in entrepreneurship. The Community Service Program (PKM) uses an educational-persuasive approach to increase youth's knowledge and skills in utilizing IoT for start-up-based independent entrepreneurship. The training held, including IoT application simulations, showed an increase in participants' knowledge and abilities. Evaluation results based on questionnaires show that the majority of participants felt a significant increase in their understanding of IoT material and applications. In conclusion, this program succeeded in developing technology-based entrepreneurial competencies for teenagers, while providing practical insight into the application of IoT in business.